Pengaruh Model Pembelajaran Flipped Classroom Di Masa Pandemi Covid 19 Terhadap Hasil Belajar IPA Sekolah Dasar - Vivi Alynda Sari; Fitria Wulandari (JURNAL HANDAYANI PGSD FIP UNIMED, 2022)
Abstract. The purposes of this study are to determine whether there is an effect of the flipped classroom learning model during the covid 19 pandemic on the science learning outcomes of fifth grade students at MI Al Abror Pekauman and to determine how much influence the flipped classroom learning model during the covid 19 pendemic has on the science learning outcomes of fifth grade students at MI Al Abror Pekauman . This research uses experimental quantitative research using the Pre Experimental – One Group Pretest Posttest Design. The results showed that there was a positive and significant effect of the flipped classroom learning model on the science learning outcomes of fifth grade students of MI Al Abror Pekauman, as evidenced by the value of 7,184 > 2.064 and the magnitude of the effect can be seen from Cohen's d calculations which show the results of 1,44 > 0.8. The conclusion of this study is that there is a large positive and significant effect between the flipped classroom learning model on the science learning outcomes of fifth grade students at MI Al Abror Pekauman.Keywords: Covid 19 Pandemic, Flipped Classroom Learning Model, Science Learning OutcomesAbstrak. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran flipped classroom di masa pandemi covid 19 terhadap hasil belajar IPA siswa kelas V MI Al Abror Pekauman dan untuk mengetahui seberapa besar pengaruh model pembelajaran flipped classroom di masa pandemi covid 19 terhadap hasil belajar IPA kelas V MI Al Abror Pekauman. Penelitian ini menggunakan jenis penelitian kuantitatif eksperimen dengan menggunakan desain penelitian pre experimental – one group pretest posttest design. Hasil penelitian ini menunjukkan terdapat pengaruh positif dan signifikan model pembelajaran flipped classroom terhadap hasil belajar IPA siswa kelas V MI Al Abror Pekauman, dibuktikan dengan nilai thit 7,184 > ttab 2,064 dan besarnya pengaruh dapat dilihat dari perhitungan Cohen’s d yang menunjukan hasil 1,44 > 0,8. Kesimpulan penelitian ini adalah terdapat pengaruh positif dan signifikan yang besar antara model pembelajaran flipped classroom terhadap hasil belajar IPA siswa kelas V MI Al Abror Pekauman.Kata Kunci: Pandemi Covid 19, Model Pembelajaran Flipped Classroom, Hasil Belajar IPA